Household cost incurred by households of female breast cancer patients followed-up in the government health sector of Western Province, Sri Lanka - Prasantha Arumapperuma; Samitha Ginige; Sujeeva Weerasinghe (College of Community Physicians of Sri Lanka, 2022)
Introduction High health care cost is a problem, even in the context of free health in Sri Lankan. Only limited evidence is available on the household cost incurred by cancer patients and none available on breast cancer patients. Objective: To assess the household cost of breast cancer incurred by households of female breast cancer patients followed up in the government health sector, in the Western province. Methods A descriptive cross-sectional study was carried out among breast cancer patients, residing in Western Province and followed up at Cancer Institute Maharagama. Random Samples of 106, 106, and 120 were selected out of eligible patients who were in the initial, 2nd to 6th, and 7th to 10th treatment years respectively. Data collection was done using a validated pre-tested interviewer administrated questionnaire. Household cost incurred by breast cancer patients, associated factors were assessed. Results The total monthly household cost incurred by households of breast cancer survivors during initial, 2nd to 6th, and 7th to 10th treatment years were Rs. 13,365.32 (SD=28,749.3), Rs. 9032.12 (SD=11,259.2) and Rs. 1835.40 (SD=5,379.1); out of which 62.9%, 70.7%, and 40.6% were direct costs respectively. Catastrophic expenditure was present among 65.6%(n=59), 52.2% (n=49), and 5.7% (n=5) of the households in the initial, 2nd to 6th, and 7th to 10th treatment years respectively. Family income less than Rs 30,000 (P